The Effects of Critical Audit Matter Paragraphs in the Audit Report on Commercial Loan Officers’ Decision to Grant Credit - Randle, Edward Charles (Journal of Accounting and Finance, 2020)
This study examines whether Critical Audit Matter paragraphs (CAMs) affect a lending decision. I use commercial lending officers (CLOs) to answer the call for additional research that examines the decision usefulness of CAMs by sophisticated users and the unintended consequences therein (Bédard et al., 2016). This study uses a 1 × 3 between-subjects experimental design. CLO participants are randomly assigned to one of three experimental conditions (1. CAM auditor provided, 2. CAM management provided, 3. NO CAM). Results suggest CAMs are decision-useful to CLOs. Evidence from this study suggests CAMs lowers the probability of a CLO to approve a loan.